Influence of silver addition on the morphological and thermal characteristics of nickel oxide-samarium doped ceria carbonate (NiO-SDCC) composite anode - Ng, Kei Hoa; Abd. Rahman, Hamimah; Somalu, Mahendra Rao (UTHM Publisher, 2018)
Addition of silver (Ag) as an electro-catalyst has been widely investigated to enhance the cathode performance for intermediate-to-low temperature solid oxide fuel cells. Ag is seldom incorporated into composite anode materials, especially for low temperature application. Therefore, this study aimed to investigate the effects of a small amount of Ag on the microstructure and thermal behaviour of nickel oxidesamarium-doped ceria carbonate (NiOSDCC) composite pellets. A high-speed ball milling technique was employed to prepare the NiOSDCC composite anode powder. Subsequently, a small amount of Ag (1, 3, and 5 wt.%) was added into NiOSDCC composite powder via ball milling. The pellets were manually pressed and sintered at 600 °C. Characterisation of the composite anodes included X-ray diffraction, Fourier transform infrared spectroscopy (FTIR), energy-dispersive spectroscopy, scanning electron microscopy, dilatometry and porosity measurement. NiOSDCC maintained good chemical compatibility regardless of Ag loading. FTIR analysis also verified the presence of carbonates, suggesting that Ag did not influence the carbonate bonding in all NiOSDCC. The porosity of all composite anodes was maintained within the satisfactory level for good anode performance (20%40%). The thermal expansion of the composite samples matched well with the SDCC electrolyte. This finding indicated that the addition of small Ag loading into NiOSDCC was within the acceptable range, demonstrating promising potential as low-temperature solid oxide fuel cell composite anode